TINJAUAN SANKSI ADMINISTRASI KETERLAMBATAN PEMBUATAN FAKTUR PAJAK (STIE Mahardhika, 2021)
One of the administrative sanctions in taxation in the form of fines is in Article 14 paragraph (4) of the General Provisions and Tax Procedures Act, which states that taxable entrepreneurs or Entrepreneurs who make tax invoices, but are not on time, are required to pay tax which is payable, subject to a fine of 2% of the tax base. The purpose of this paper is to review these provisions. The research method used is descriptive qualitative. The results of the study found that administrative sanctions are fines for the delay in making tax invoices even though the making is still in the current month. Fines are also sanctions imposed on violations by taxpayers in the form of errors or negligence related to the fulfillment of tax obligations which result from such violations generally do not harm the state. Based on the research, it was found that there was an assumption that the sanctions were deemed unfair so that it needed to be reviewed whether the tariff needed to be changed or with other solutions.